Modeling the Effects of Customer Trust and Satisfaction on Behavioral Intention among E-Commerce Users in Makassar - Charence Edina Immanuel; Lusiana Luoran Lie; Muhammad Hawari; Angelique Leticia Liliputra; Sanusi Rezka Mulya; Firman, Afrizal (Business and Entrepreneurial Review, 2025)
This study examines the impact of customer trust and customer satisfaction on customer behavior intention within the e-commerce sector in Makassar. The Quantitative analysis with 100 respondents and SmartPLS 4.1 for structural equation modeling indicates that customer trust does not exert a substantial direct influence on customer behavior intention, suggesting that trust primarily serves as a foundational expectation rather than a catalyst for purchasing behavior. In fact, customer satisfaction exhibits a robust and large positive influence on customer behavior intentions, illustrating the viral role of service quality, precise product delivery, and the whole shopping experience in influencing consumer behavior. The results indicate that in a developed e-commerce environment, customer happiness is the principal factor influencing behavioral intention, whereas trust functions as a fundamental prerequisite rather than a driving force. The study offers actionable insights for e-commerce managers to focus on techniques that enhance customer satisfaction and suggests directions for future research to include wider variables and diverse regional contexts.